Mental health symptoms and verbal fluency in elderly people: Evidence from the Spanish longitudinal study of aging. (3rd June 2019) - Simpson, Ian Craig; Dumitrache, Cristina Gabriela; Calet, Nuria
ABSTRACT: Objectives: Depression and loneliness are highly prevalent in old age. Moreover these mental health symptoms adversely affect the verbal fluency of the elderly. We examined the relationship between depression and loneliness with verbal fluency in people aged 50 years or older. Method: Research data were collected during the pilot study of the Longitudinal Aging Study in Spain (ELES) in which a representative sample of non-institutionalized Spanish older people was assessed. Here, the cross-sectional data for 962 participants were analysed using hierarchical regressions, controlling for age, education level, overall cognitive functioning, social networks and satisfaction with family. Results: Higher levels of cognitive functioning were associated with higher verbal fluency. Females showed higher levels of phonological fluency. Neither depression nor loneliness were significant predictors of phonological fluency but loneliness was a significant predictor of semantic fluency. For mild levels of loneliness, the rate of decline in semantic fluency slows in the oldest ages. In contrast, for severe loneliness the rate of decline in semantic fluency increases in the oldest ages. Conclusions: Depressive symptoms, loneliness and cognitive impairment are all prominent in ageing and therefore their impact on ageing needs to be better understood. Early detection of loneliness, along with the implementation of intervention for individuals diagnosed with loneliness is advisable in order to avoid negative repercussions for the verbal fluency of these individuals.